A Prospective Study of Safety Profile and Efficacy of three doses of Intravitreal Bevacizumab in Diabetic Macular Edema - Y, Nasrin; Ajay, Sharma; Yalakala, Sharmila (International Journal of Retina, 2021)
Introduction: Current study aimed to evaluate efficacy of intravitreal Bevacizumab in Diabetic macular edema, and to identify their ocular and systemic complications if any. Method: It is a prospective, interventional study with 68 patients in 82 eyes with Diabetic macular edema. All treated by 3 injection of intravitreal bevacizumab with 1 month interval. Visual acuity, macular edema, and complications evaluated at every month upto 6th months. Ranibizumab was offered if the patient is a non-respondent to Bevacizumab. Results: Majority age group of 61-70 years with a mean age of 59 ± 6.72 years. The mean duration of diabetes was 11.68 ± 7.2 years. The mean baseline BCVA and CRT are 0.64 ± 0.28 Log MAR units and 436.99 ± 135.10 μm. After 3 injections, BCVA values are 0.48±0.27 (p< 0.01)), 0.36±0.24 (p<0.01)), and 0.27±0.24 (p<0.01), 0.23±0.27 Log MAR (p<0.01)) at 1month, 2 months, and 3 months, and 6 months follow-up respectively. CMT levels are 315.79±124.60 μ at 1 month, after 3rd IVA and this significant change (p<0.01) followed with subsequent follow-up with mean CRT of 296.04±122.97 μ (p< 0.01) at 6th month. The BCVA improved ≥ 2 Snellen lines in 69.5% and 78% cases, resolution of CMT in 56% and 69.5% cases at 3 months and 6 months respectively. At the end of the 3rd month, 46 eyes macular edema completely resolved with 3 injections of IVA, 23 eyes persistent macular edema present, 13 eyes refractory to bevacizumab injections. Persistent & Refractory macular edema eyes (36) switched to Ranibizumab injections.In persistent macular edema, significant resolution (p≤0.01) of macular thickness (370.52 ± 71.43 µm vs. 341.08 ± 122.75 µm) without (p=0.09) improvement in visual acuity (0.45 ± 0.20 vs. 0.34 ± 0.23) was observed post Ranibizumab injections. In Refractory macular edema, thickness of cases no significant (497.76 ± 161.07µm vs 407.84 ± 169.64 µm) improvement seen after Ranibizumab injections(p=0.1). Recurrence of macular edema seen in 10.9%. Subconjunctival haemorrhage seen in 10.9%-12.1% cases, raised IOP in 2.4%-3.6% cases at post injection day 1. No other ocular and systemic complications were observed during follow-up. Conclusions: Intravitreal bevacizumab is effective in treatment of diabetic macular edema but therapeutic effect is temporary and repeat treatment is needed. It does not show any potential drug related ocular and systemic side effects, hence it is safe and economical therapeutic agent